2019
DOI: 10.1590/1980-549720190010.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da função renal na população adulta brasileira, segundo critérios laboratoriais da Pesquisa Nacional de Saúde

Abstract: RESUMO: Objetivo: O presente estudo avaliou a função renal da população adulta brasileira, segundo critérios laboratoriais da Pesquisa Nacional de Saúde (PNS). Metodologia: Estudo descritivo realizado com os dados laboratoriais da PNS, coletados entre os anos de 2014 e 2015. Com base nos dados laboratoriais foram analisadas prevalências populacionais de creatinina sérica (CR) e estimativa da taxa de filtração glomerular (TFG), segundo variáveis sociodemográficas. Resultados: A amostra foi de 8.535 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 17 publications
0
17
0
20
Order By: Relevance
“…Studies with laboratory data allow estimating the prevalence of health problems in subclinical stages and populations with less access to health services, and therefore, still without diagnosis and treatment. For example, recent studies with PNS laboratory data have already shown a high prevalence of chronic renal failure 30 and diabetes 15 , compared to self-reported measures. The most prevalent MetS components were high WC followed by low HDL cholesterol in both genders, but with higher prevalence among women and any age group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with laboratory data allow estimating the prevalence of health problems in subclinical stages and populations with less access to health services, and therefore, still without diagnosis and treatment. For example, recent studies with PNS laboratory data have already shown a high prevalence of chronic renal failure 30 and diabetes 15 , compared to self-reported measures. The most prevalent MetS components were high WC followed by low HDL cholesterol in both genders, but with higher prevalence among women and any age group.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates indicate overall prevalence of CKD (stages 1 to 5) in 14.3% in the general population and 36.1% in risk groups 2 . In Brazil, the estimated prevalence of CKD (stages 3 to 5) in adults is 6.7%, tripling in individuals aged 60 years or older 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A baixa renda, por sua vez, constitui um fator que dificulta ainda mais o acesso dessa população aos serviços como um todo, refletindo diretamente em necessidades que vão desde o transporte do paciente para as sessões de diálise (que muitas vezes ocorrem em outro município) até a compra de medicamentos e insumos que, eventualmente, não são distribuídos (ou estão em falta) no sistema público de saúde. Ressalta-se que a maioria dos pacientes em urgência dialítica recorrem ao SUS para realizar seu tratamento (3) .…”
Section: Discussionunclassified
“…O equilíbrio da química interna do corpo humano se deve, em grande parte, ao trabalho dos rins e qualquer alteração nas funções desses órgãos pode gerar um desequilíbrio no organismo, tornando indispensável o estabelecimento de uma terapia renal substitutiva (TRS). Este decréscimo das funções renais é denominado insuficiência renal (IR), que pode ser classificada em insuficiência renal aguda (IRA) ou insuficiência renal crônica (IRC) e geralmente se desenvolvem a partir do manejo inadequado de doenças crônicas, como a Diabetes Mellitus (DM) e a Hipertensão Arterial Sistêmica (HAS) (1)(2)(3) .…”
Section: Introductionunclassified